The effect of continuous exposure to electromagnetic fïeld on four successive generations of mice (Faculty of Medicine Universitas Indonesia, 2002)
The objective of this study is to know the biobgical effects of electromagnetic field treatment on four successive generations of mice. Fourty eight male and female mice of Swiss Webster Strain, 3 months of old, and 35 - 40 g body weight, were kept in a controlled environment and fed a standard diet. Mice were divided into 6 groups of four couples each. The first group was exposed to electromagnetic field of I kV/10 cm, the second group to 2 kV/10 cm, and the third group to 3 kV/10 cm. The remaining 3 groups were served as untreated controls of the first, second, and third group, respectively. Each couple of mice was placed in a cage (26x20x11 cm) with wire metal cage tops. The cages of experimental groups with mice inside, were then put on the negative terminal plate of a pair of parallel aluminium plate electrodes. These cages were perpendicular to the positive electrode plate at a distance of I0 cm. Subsequently, the electrodes were connected to stepup transformer as an alternating current power supply. All mice belonging to experimental and untreated control groups were allowed to mate, gastate, and deliver the first up to fourth generations, During investigation, all generations of experimental groups were continuously treated to electromagnetic field, while generations of untreated control groups received no treatment to electromagnetic field, During the study, all mice were housed in a room having a temperature of 26o C and a light - dark cycle of 12:12 hours. The results of this study showed that exposure of mice to electromagnitic field results in reduced fertility with no change in sex ratio of the offspring. Exposure to electromagnetic field, however, were effective in inducing congenital anomalies, such as micropthalmy, white eyes, short hind legs, dwarf mice, and tumors in both sexes of the offspring which caused of death after 3 - 4 months of old. A large mortality rate were found, especially in the third and fourth generations. No congenital anomalies and tumors were noted in untreated controls. ln conclusion, we suggest that several facts which found in this study were the result of changes in genetic material of the sperm or eggs during spermatogenesis or oogenesis, respectively, i.e. a mutagenic effect. This interaction between electromagnetic field and the living cell, may then cause biological effects on cells, tissues, and organs, so that finally there are consequences for the whole organisms. (Med J Indones 2002; 11: 3-10) Keywords: electromagnetic field, fertility, mortality rate, congenital anomalies, tumor, mice